Interspecies Mothering in the Anthropocene: Discourse of Transcorporeality and Matricentricity in Charlotte McConaghy’s Migrations and Barbara Kingsolver’s Flight Behaviour - V. Janane; Rebecca, S. Christina (The Grove - Working Papers on English Studies, 2024)
The research paper aims to disrupt the dominant anthropocentric notions of motherhood that focuses on the multigenerational praxis of human to human relationships, and instead sheds light on the ecological motherhood, that accommodates diverse relationships between women and the more than human. This hetero-patriarchal reading challenges anthropocentric personhood and transitions towards the motherhood in anthropogenic narratives like Migrations and Flight Behaviour that perceives motherhood as multispecies inclusive and transcorporeal. The novels deal with ecological mothering that enables the mothers as well as their children- Arctic Terns in Migrations and Monarch Butterflies in Flight Behaviour, in survival and sustenance. The mothering offered by the women in the climate narratives radically debunks the process of ‘othering’ of the more than human by putting forth ‘other-mothering’ (Collins and Michaels) that promotes cohabitation and multispecies justice. The paper will further investigate the emotional and ecological praxis of motherhood amidst the anthropogenic toxification of global warming, species extinction and relocation. The Motherhood environmentalism by Dellarobia in Flight Behaviour and Franny in Migrations will be scrutinised as a call for kinship and multispecies justice.